The Influence Of User Experience, E-Service Quality, And E-Trust Mediated By E-Satisfaction On E-Loyalty: Customers Subscription Video On Demand (Svod) - Helen Karmelia; Kandi Sofia Senastri Dahlan (Journal Of Social Science (JoSS), 2024)
Currently in the digital era, the internet plays a very important role in supporting and making it easier for people to carry out their daily activities through various technologies. One of the benefits of the internet in the entertainment sector is being able to watch movies or online shows and streaming subscription videos, besides that this activity is one of the most popular activities in the community that is carried out during and after the pandemic. This study aims to analyze the influence of User Experience, (E-Service Quality), E-Trust, mediated by E-Satisfaction, on E-Loyalty on Subscription Video on Demand (SVOD) customers during the Covid-19 pandemic to after the Covid-19 pandemic in the Greater Jakarta area. This study is a quantitative study by collecting 278 samples. Data collection was carried out by distributing questionnaires online and the scale used was the Likert scale. The data analysis technique used is Structural Equation Modelling (SEM) with Smartpls 3.0 software. The results of this study show that User Experience has a significant influence on E-Satisfaction and E-Loyalty, E-Service Quality has a significant influence on E-Satisfaction directly but does not have a significant influence on E-Loyalty directly, E-Trust has a significant influence on E-Satisfaction directly but does not have a significant influence on E-Loyalty directly, and E-Satisfaction has a significant influence on E-Satisfaction directly, and E-Satisfaction has a significant influence on E-Satisfaction and E-Loyalty. significant influence on E-Loyalty. E-Satisfaction has succeeded in mediating between User Experience, E-Service Quality, and E-Trust with E-Loyalty.